2002
DOI: 10.1207/s15327914nc422_10
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Treatment With Benzyl Isothiocyanate, a Strong Bladder Promoter, Inhibits Rat Urinary Bladder Carcinogenesis by N-Butyl-N-(4-Hydroxybutyl)Nitrosamine

Abstract: Effects of benzyl isothiocyanate (BITC) on urinary bladder carcinogenesis were examined in rats simultaneously treated with N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN). Groups of 20 6-wk-old Fischer 344 male rats were given 10, 100, or 1,000 ppm BITC in the diet or a basal diet with 50 ppm BBN in the drinking water for 40 wk and then killed for autopsy. Additional groups consisting of 10 or 9 rats were similarly given BITC or the basal diet alone without BBN treatment. With BBN treatment, dysplasia, papilloma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…However, some other ITC have been reported to be carcinogenic in rats. [27][28][29][30][31][32] Especially, allyl isothiocyanate was reported to be carcinogenic for male F344 rats in the urinary bladder, but was not carcinogenic for B6C3F1 mice of either gender. 27 High cruciferous vegetable consumption is suggested to reduce bladder cancer risk from epidemiological study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some other ITC have been reported to be carcinogenic in rats. [27][28][29][30][31][32] Especially, allyl isothiocyanate was reported to be carcinogenic for male F344 rats in the urinary bladder, but was not carcinogenic for B6C3F1 mice of either gender. 27 High cruciferous vegetable consumption is suggested to reduce bladder cancer risk from epidemiological study.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, PEITC treatment did not affect the BBN-induced bladder tumorigenesis and PHITC suppressed bladder tumor development. Okazaki et al 32 found that simultaneous treatment of BITC and BBN inhibits BBN-induced urinary bladder carcinogenesis in F344 rat. Those findings suggest that modifying effects of ITC on the urinary bladder carcinogenesis are depended to the difference of rodent species and strains, chemicals and treatment schedule.…”
mentioning
confidence: 99%
“…Using a cell culture system, we previously showed that dietary isothiocyanates and their urinary metabolites (NAC-ITCs) exerted potent antiproliferative effects on human bladder cancer cells at in vivo -achievable concentrations (4-7). The induction of carcinogendetoxifying phase 2 enzymes and the inhibition of carcinogen-induced carcinogenesis in the bladder of animals has also been reported (8,9). It is highly possible that intake of isothiocyanate-rich cruciferous vegetables has a preventive effect on human bladder cancer, and such protective effects may, to a certain extent, correspond to the amount of isothiocyanates provided by these vegetables.…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 93%
“…Bladder cancer is particularly interesting because dietary isothiocyanates, a group of key anticarcinogens occurring in cruciferous vegetables, show potent chemopreventive effects against bladder cancer in both in vitro and in vivo models (4)(5)(6)(7)(8)(9). Moreover, the unique in vivo pharmacokinetics and disposition of orally ingested isothiocyanates in humans renders the bladder the best targeted organ for the anticancer effect of dietary isothiocyanates (5).…”
Section: Introductionmentioning
confidence: 99%
“…These bioactive compounds act via multiple mechanisms, such as cancer cell signalling, proliferation, apoptosis, migration and invasion, as well as angiogenesis and carcinogen elimination , Zhang, 2004, Thornalley, 2002, Nakamura and Miyoshi, 2006, Wu et al, 2009, Navarro et al, 2011, Wahle et al, 2011, Soobrattee et al, 2006, Tanaka et al, 2012, Van Breemen and Pajkovic, 2008, to exhibit in vitro and in vivo anticancer activities. BG: 12.7 µmol/g seed, < 0.03 µmol/g pulp BITC: 4.6 µmol/g seed, < 0.003 µmol/g pulp (Nakamura et al, 2007) In vivo animal studies in rat, mouse or hamster for inhibitory effect on:  intestinal carcinogenesis (Sugie et al, 1994)  hepatocarcinogenesis (Sugie et al, 1993)  lung tumourigenesis and metastasis (Kim et al, 2011a, Hecht et al, 2000, Hecht et al, 2002  pancreatic carcinogenesis (Kuroiwa et al, 2006)  urinary bladder carcinogenesis (Okazaki et al, 2002)  mammary carcinogenesis (Warin et al, 2009).…”
Section: Phytochemicals In Carica Papaya With Reported Anticancer Actmentioning
confidence: 99%